An investigation into the vietnamese translation of nominal groups describing nature in the series of “little house” by laura ingalls wilder and “wuthering heights” by emily bronte - Hồ Thị Huyền Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis attempts to shed light on the problems involved in the act of translating nominal groups (NGs) describing nature in ‘A Little House’ by Laura Ingalls Wilder and ‘Wuthering Heights’ by Emily Bronte into Vietnamese. The study has its theoretical underpinning based on theories of translation procedures proposed by Vinay and Darbelnet (1995), Catford’s model of translation shifts (2000), and the nominal group structures introduced by Halliday (1985). Through such linguistic and translation theories proposed by predecessors, the study attempts to accentuate some certain relation between text analysis and translation. Such aspects of translation, be they translation procedures and translation shifts, have been used as analytical tools for the analysis made in the Vietnamese translation of NGs describing nature in the named literary texts. A sample of 200 of English NGs describing nature in the corpus were analyzed basing on Vinay and Darbelnet’s approaches of translation procedures (literal translation, transposition, modulation, and adaptation) as well as Catford’s translation shifts (level shift and category shift). Interesting findings regarding the adjustments and modifications made by the translator in the target language (TL) text signify the inevitable tendency of utilising certain procedures and shifts in the act of rendering meaning from English into Vietnamese. Some conclusions were then drawn and implications put forward with respect to tentative solutions that need to be carefully considered for the delicate analysis of the literary texts to figure out ways in which the translator has used - different procedures, structures, and approaches – for ‘equivalent effect’ in translation.